Arecoline Is Associated With Inhibition of Cuproptosis and Proliferation of Cancer-Associated Fibroblasts in Oral Squamous Cell Carcinoma: A Potential Mechanism for Tumor Metastasis - Li, Jinfei; Chen, Shuangyi; Liao, Yuxuan; Wang, Hongyi; Zhou, Dawei; Zhang, Bo (Frontiers in Oncology, 2022)
Background: Metastatic disease remains the primary cause of death for patients with oral squamous cell carcinoma (OSCC), especially ones with betel nut use. The different steps of the metastatic cascade rely on reciprocal interactions between cancer cells and tumor microenvironment (TME). Cancer-associated fibroblasts (CAFs) are regarded as a significant component in TME of OSCC. However, the precise mechanisms regulating CAFs in OSCC are poorly understood. Methods: Thirteen genes related to the arecoline were analyzed to explore the significant ones involved in arecoline-related OSCC metastasis. The GSE139869 (n=10) and TCGA-OSCC data (n=361) were mined respectively for the identification of the differentially expressed genes. The least absolute shrinkage and selection operator (LASSO) regression was performed to identify the independent prognostic signatures. GO and KEGG were conducted to explore the functional enrichment of selected genes and gene set enrichment analysis of cuproptosis-related genes were completed. Spearman analysis and TIMER were used to visualize the correlation between the infiltration of CAFs and the gene expression. The correlation analysis of the cells and different genes, including CAFs infiltration and transcripts per million expression, was assessed. The relationship between arecoline and CAFs was confirmed by CCK-8. CancerSEA was performed to identify the single-cell phenotype. Result: Arecoline-associated-fibrosis relative-oral cancer differential expression genes (AFOC-DEGs), namely PLAU, IL1A, SPP1, CCL11, TERT, and COL1A2, were screened out and selected from the GEO database and TCGA database. AFOC-DEGs were highly expressed in OSCC, which led to poor survival of patients. Functional enrichment analysis, protein-protein interaction network construction, and Spearman correlation analysis all suggested that AFOC-DEGs were closely associated with cuproptosis. Cellular experiments demonstrated that arecoline stimulation could significantly increase the cell viability of CAFs. SsGSEA results showed that GLS and MTF1 were highly expressed when fibroblasts proliferated at high enrichment levels. In addition, analysis of single-cell sequencing results suggested that OSCC cells with high expression of AFOC-DEGs were associated with OSCC metastasis. Conclusion: We found a close association between arecoline, cuproptosis, and CAFs, which might play an important role in the metastasis of OSCC.